2005
DOI: 10.1616/1476-2137.14184
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of green tea catechins

Abstract: Extracts of leaves from the tea plant Camellia sinensis contain polyphenolic components with activity against a wide spectrum of microbes. Studies conducted over the last 20 years have shown that the green tea polyphenolic catechins, in particular (-)-epigallocatechin gallate (EGCg) and (-)-epicatechin gallate (ECg), can inhibit the growth of a wide range of Gram-positive and Gram-negative bacterial species with moderate potency. Evidence is emerging that these molecules may be useful in the control of common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
260
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(277 citation statements)
references
References 78 publications
7
260
1
9
Order By: Relevance
“…The literature has reported many different properties of this tea against dental caries due to presence of their catechins [32][33] . Furthermore, green tea has components which can inhibit matrix metalloproteinase that are present on saliva and on mineralized dental tissues 34 decreasing the dental erosion/ abrasion in situ 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The literature has reported many different properties of this tea against dental caries due to presence of their catechins [32][33] . Furthermore, green tea has components which can inhibit matrix metalloproteinase that are present on saliva and on mineralized dental tissues 34 decreasing the dental erosion/ abrasion in situ 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other authors have found that the broth assay were more efficient than agar assays for a large number of antibiotics (Baker, Stocker, Culver, & Thornsberry, 1991). According to Hara (2001), the EGC, EGCG and ECG catechins seem to be the most potent antibacterial agents and the activity of catechins alone is reported to be modest (Taylor, Hamilton-Miller, & Stapleton, 2005). Hence, the observed results may be considered as a synergistic effect between the different compounds found in green tea.…”
Section: Resultsmentioning
confidence: 97%
“…drymifolia), así como su perfil fitoquímico funcional. (Motamedi et al, 2014;Bezerra dos Santos et al, 2015, Taylor et al, 2005. La actividad bactericida puede deberse en parte a la presencia de saponinas; estos compuestos tienen la capacidad de romper las membranas de los microorganismos modificando la tensión superficial del medio extracelular (Nassiri y Hosseinzadeh, 2008).…”
Section: Discusión Y Conclusiónunclassified